2016
DOI: 10.1051/e3sconf/20160708001
|View full text |Cite
|
Sign up to set email alerts
|

Heavy rainfall: An underestimated environmental risk for buildings?

Abstract: Abstract. Although impacts of heavy rain on buildings in urban areas are often extensive, the public usually underestimates the negative consequences of that environmental risk compared e.g. to storm or hail events. However, the intensification of extreme weather events due to climate change as well as the rising physical vulnerability of assets are going to trigger the increase of impacts on the built environment. Heavy rain events are often highly localised that makes it difficult to estimate their probabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 2 publications
0
8
2
Order By: Relevance
“…Floods in the western part of Norway (where Bergen is located) are mainly caused by heavy rainfall during the autumn season (Roald, 2008). The Norwegian Center for Climate Services report pointed out that rainfall-dominated floods are projected to increase by almost 60 % (with RCP8.5 scenario) towards the end of the century, and more frequent and stronger intense rainfall events may in the future present special challenges in small, steep rivers being fed by small upland catchments (Hanssen-Bauer et al, 2015). Vormoor et al (2015) found that autumn-winter events will become more frequent by 2099, which will lead to an intensification of the current autumn-winter flood regime for the coastal catchments in Norway.…”
Section: Study Areamentioning
confidence: 99%
See 4 more Smart Citations
“…Floods in the western part of Norway (where Bergen is located) are mainly caused by heavy rainfall during the autumn season (Roald, 2008). The Norwegian Center for Climate Services report pointed out that rainfall-dominated floods are projected to increase by almost 60 % (with RCP8.5 scenario) towards the end of the century, and more frequent and stronger intense rainfall events may in the future present special challenges in small, steep rivers being fed by small upland catchments (Hanssen-Bauer et al, 2015). Vormoor et al (2015) found that autumn-winter events will become more frequent by 2099, which will lead to an intensification of the current autumn-winter flood regime for the coastal catchments in Norway.…”
Section: Study Areamentioning
confidence: 99%
“…statenskartverk.no/ (last access: 29 August 2019). The definition of small rural catchments is based on the report by Fleig and Wilson (2013) applying an upper area limit of 50 km 2 . The catchments were selected for this impact study because there are critical infrastructures (e.g., culverts, bridges, and buildings) at the outlet of the catchments which could be damaged by floods in the future period (2070-2100).…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations